Rare epiphytic lichens in phytocenoses of anthropogenic disturbed territories and their application in bioindication (Moscow region) - Aristarkhova, E. A.; Suslova, E. G. (Проблемы ботаники Южной Сибири и Монголии, 2020)
The article analyzes the ecology and distribution of species of genera: Bryoria Brodo et D. Hawksw., Ramalina Ach., Usnea Dill. ex Adans., found in Moscow region and listed in the red book of the region (2018). It is based onliterature materials and monitoring data that we conducted as part of the «Verkhovye» Nature protection Fund in 2010–2019.In the period from 1906 to 1995, a greater number of Ramalina species were cited for Moscow region than at present,some of the finds of Usnea species were made on the outskirts of Moscow and in the near Moscow region, meanwhile thedistribution of genus Bryoria was not studied. Currently, the most favorable conditions for the development of lichens areformed in the North, West and North-West of the Moscow region, where the largest number of finds of various specieswith maximum abundance is noted. In the South-east, their settlement is probably hindered by dust, increased dryness ofthe air and the presence of harmful compounds in the atmosphere. In their distribution, lichens prefer intact habitats withhigh humidity and minimal air pollution: large fragments of preserved protected old-growth forests (spruce and sprucesmall-leaved), swampy forests and forest swamps.For the most common species with a high abundance (Bryoria fuscescens (Gyeln.) Brodo et D. Hawksw. и B. capillaris (Ach.) Brodo et D. Hawksw., Usnea hirta (L.) Weber ex F. H. Wigg.и др.), it is possible to track the dynamics ofchanges in the environment. The rarest species are recommended to keep category 1–2 in the Red book of the Moscow region (Bryoria nadvornikiana (Gyeln.) Brodo et D. Hawksw., B. vrangiana (Gyeln.) Brodo et D. Hawksw., B. osteola(Gyeln.) Brodo et D. Hawksw., Usnea lapponica Vain. и др.).